A framework for the practical science necessary to restore sustainable, resilient, and biodiverse ecosystems. Issue 4 (15th December 2016) - Miller, Ben P.; Sinclair, Elizabeth A.; Menz, Myles H. M.; Elliott, Carole P.; Bunn, Eric; Commander, Lucy E.; Dalziell, Emma; David, Erica; Davis, Belinda; Erickson, Todd E.; Golos, Peter J.; Krauss, Siegfried L.; et al.
Abstract: Demand for restoration of resilient, self‐sustaining, and biodiverse natural ecosystems as a conservation measure is increasing globally; however, restoration efforts frequently fail to meet standards appropriate for this objective. Achieving these standards requires management underpinned by input from diverse scientific disciplines including ecology, biotechnology, engineering, soil science, ecophysiology, and genetics. Despite increasing restoration research activity, a gap between the immediate needs of restoration practitioners and the outputs of restoration science often limits the effectiveness of restoration programs. Regrettably, studies often fail to identify the practical issues most critical for restoration success. We propose that part of this oversight may result from the absence of a considered statement of the necessary practical restoration science questions. Here we develop a comprehensive framework of the research required to bridge this gap and guide effective restoration. We structure questions in five themes: (1) setting targets and planning for success, (2) sourcing biological material, (3) optimizing establishment, (4) facilitating growth and survival, and (5) restoring resilience, sustainability, and landscape integration. This framework will assist restoration practitioners and scientists to identify knowledge gaps and develop strategic research focused on applied outcomes. The breadth of questions highlights the importance of cross‐discipline collaboration among restoration scientists, and while the program is broad, successful restoration projects have typically invested in many or most of these themes. Achieving restoration ecology's goal of averting biodiversity losses is a vast challenge: investment in appropriate science is urgently needed for ecological restoration to fulfill its potential and meet demand as a conservation tool.